TEKNIK IRIDOLOGI DAN KINESIOLOGI SEBAGAI ALTERNATIF MENGATASI MASALAH STRES DI SEKOLAH SEBAGAI AKIBAT PEMANASAN GOBAL - Razak, Abdul; Lardiman, Hendra (IAIN Batusangkar, 2013)
Iridology is the study of the iris of the eye. Iris is a collection of nerves that are delicate and represent and explain the whole condition of the body. Iridology last five years very rapid progress and by the authors have also developed and applied in the field of fisheries, education and human resource management field as needed. Likewise the case of Kinesiology is the study of the nerves in the arm that had been developed by the experts for the detection of various diseases and are able to explain scientifically the cause of the body's mechanism of electromagnetic waves. In 2010, researchers have been applying both the science to determine the stress level of elementary school students and its relationship with the brain and trigger real stress conditions. The results of these studies indicate that the effect is real. That is both a science or its applications in the form of both knowledge -based techniques can be used to cope with the stress of environmental conditions, including global warming.Key words: engineering , iridology , kinesiology , stress and global warming